Assessment of life quality index among patients with acne vulgaris in a suburban population - Neirita Hazarika; Radha K Rajaprabha (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Acne vulgaris affects about 85% of adolescents, often extending into adulthood. Psychosocial impact of acne on health-related quality of life (QoL) has been identified, but it remains under-evaluated, especially in Indian patients. This study was aimed to assess the impact of acne and its sequelae on the QoL. Materials and Methods: This was a hospital-based, prospective, cross-sectional study done between June and November 2014 on 114 consenting patients above 15 years of age with acne vulgaris. Acne vulgaris and its sequelae were graded, and QoL was assessed by using Dermatology Life Quality Index (DLQI) questionnaire. Results: Most cases (64%) were between 15 and 20 years. Females (57%) outnumbered males. Facial lesions (61.4%) and grade II acne were most common. Mean DLQI score was 7.22. DLQI scores were statistically influenced by the age of the patient, duration and grade of acne, acne scar, and postacne hyperpigmentation. Conclusion: This study showed significant impairment of QoL in acne patients. Assurance and counseling along with early treatment of acne vulgaris are important to reduce disease-related psychosocial sequelae and increase the efficacy of treatment.